Instability of the production of avermectins, sporulation, and pigmentation in Streptomyces avermitilis - Novák, J; Kopecký, J; Kofronová, O; Vanĕk, Z (Canadian journal of microbiology, 1993)
Production of avermectins, sporulation ability, and colony pigmentation were followed in Streptomyces avermitilis C-18/6 cultures during serial transfer (for eight subcultures) in four different liquid media. These phenotypes were found to be unstable and independent of each other. A procedure was established whereby depressed avermectin production could be reversed but the degree of reversion was dependent on the history of the isolate, i.e., the type of medium used. The presence of isoleucine as the sole N source caused an immediate loss of avermectin production and this could not be reversed.
Keywords: Pigmentation; Microscopy, Electron, Scanning; Phenotype; spory bakteriální; pigmentace; Ivermectin; Spores, Bacterial; fenotyp; Streptomyces; ivermektin; mikroskopie elektronová rastrovací